Genome engineering in human pluripotent stem cells. (February 2017) - Parekh, Udit; Yusupova, Marianna; Mali, Prashant
Highlights: Current status, challenges and outlook for CRISPR/Cas9 genome engineering in hPSCs. Applications in investigating human biology, disease and therapy. Novel applications of dCas9-based fusions. Abstract : Human pluripotent stem cells (hPSCs) hold great promise for modeling and recapitulation of human biological processes. Coupled with the advent of genome engineering tools, specifically the CRISPR–Cas9 systems, hPSCs have opened a multitude of possibilities in modeling human biology and creating novel cellular therapies. Here, we review the fundamentals of both technologies, and the wide-ranging present and future applications of genome engineering in hPSCs.